Analyze students learning interest in the subjects they like - Siregar, Tifany Intania; Anilafiza, Ufistia; Atia, Saniatul; Lestari, Hafifah Indah (International Journal of Education and Teaching Zone, 2023)
The purpose of this study was to determine the effect of the talents and interests of students based on the subjects and teachers they liked on the students of Madrasah Ibtidaiyah Nurul Yaqin Simoang Sungai Durendan as well as on the learning outcomes and achievements of students in grade 6.B. This study used qualitative methods .population with a total sampling of 22 students/i, the most preferred subject is Corner with a total of 72%.interests in learning to follow the learning of class VI students of Madrasah Ibtidaiyah Nurul Yaqin Simpang Sungai Duren are very diverse. Starting from those who are very enthusiastic in participating in learning to those who are less enthusiastic in participating in learning. The learning interest of these students is also influenced by the way of teaching and learning methods used by the teacher. In this case, the more interesting the teaching method given by a teacher, the more enthusiastic the students will be in participating in the teaching and learning process in the classroom. Students' interest in learning is also influenced by the subjects they like and dislike. The ability of students to receive learning material is different. Therefore, it is necessary to analyze students' and students' learning interest based on their preferred subjects and teachers. This is done to improve the quality of the teacher's teaching and also to better understand the ability of students to receive learning.